Comparison of Solutions of the Nonlinear Transfer Equation - Kholkin, A.M.; Sanikidze T.A. (Журнал математической физики, анализа, геометрии, 2017)
The paper considers the evolution of nonlinear equation describing the process of energy transfer by radiation. The comparison theorem for the solutions of this equation is formulated and proved.